The anatomical bases of the 3D digital facial approximation of the Zlatý kůň 1 woman (ca. 43,000 BP) - Moraes, Cicero; Galassi, Francesco Maria; Sineo , Luca; Šindelář , Jiří; Varotto, Elena; Mietlińska-Sauter , Joanna; Antunes-Ferreira , Nathalie; Habicht, Michael E.; Beaini , Thiago (Anthropological Review, 2024)
In 1950 on Mount Zlatý kůň (‘Golden Horse’) in modern-day Czech Republic a system of caves was discovered. During many years of research in this area, human and animal osteological remains have been excavated, among which the most interesting ones were nine fragments of a female skull, now dated to ca. 43,000 yrs BP which are one of the earliest known anatomically modern humans in Eurasia. The aim of this research was to use purely digital techniques to: (1) to reconstruct the skull based on the 3D data of preserved fragments, (2) to approximate the probable appearance of the female it belonged to, and (3) to analyze the calculated shape of the reconstructed mandible and volume of the neurocranium in the context of similarities and differences with other representatives of the genus Homo. Computer techniques used in this research constitute a new, original approach to the problem of 3D analyses and may be useful primarily in bioarchaeological sciences, where metric analyses of the most valuable bone artifacts are often severely limited due to the incompleteness of the material available for research. The digital techniques presented here may also contribute significantly to the field of surgery, with the possibility of being adapted for applications in cranial prosthetics and post-traumatic reconstructive surgery.